Gerakan Salat Subuh Berjamaah sebagai Media Penguatan Semangat Keberagaman Umat Islam - Rahmadani Akbar; Rahmad Alkhadafi (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
This study explores the Subuh Congregational Prayer Movement (Gerakan Sholat Subuh Berjamaah/GSSB) in Ujung Batu District as a medium for strengthening Islamic religiosity and social solidarity. The movement emerged in response to the limited community participation in Subuh prayer compared to other congregational rituals. Conducted weekly through prayer, sermons, and communal breakfast, GSSB attracts hundreds to thousands of participants. Using a qualitative descriptive-analytical approach, data were collected through in-depth interviews, participant observation, and documentation. The analysis draws on Max Weber’s sociology of religion, focusing on how religious ethics generate discipline, responsibility, and collective spirit. The findings show that GSSB effectively achieves its objectives of reinforcing Islamic religiosity and enhancing social solidarity. Spiritually, it fosters consistency in worship and strengthens the relationship between humans and God. Socially, it promotes trust, cooperation, and a sense of belonging, while structurally it builds collaboration among religious leaders, communities, and local authorities. GSSB also illustrates Durkheim’s concept of collective effervescence, where shared rituals create emotional energy and collective identity. Moreover, it generates social capital that supports community empowerment. Thus, GSSB exemplifies how local Islamic initiatives can transform spiritual values into social cohesion, integrating religious commitment with communal harmony in contemporary Muslim society